Experimental and analysis of vehicle dynamics performance based on driving behavior / Mohd Azman Abdullah... [et al.] - Abdullah, Mohd Azman; Ibrahim, Munaliza; Abdul Rahim, Muhammad Aliff Haika (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Most of the time, the dynamic performances of a vehicle is depending on the driving behavior of the driver. The driving behavior can be analyzed from the way they control the vehicle during cornering, accelerating, braking and driving through uneven roads. This paper presents the vehicle dynamics performance analysis based on driving behavior among teenagers’ drivers. The analysis was concentrated on how they handle the vehicle that can be seen from the values of moments consists of roll, pitch and yaw and accelerations (vibrations) at x, y and z axes. From the data collected, the dynamic performances of the vehicle were analyzed based on the driving behavior. It can observed that, the aggressive drivers produced significant values in moments and accelerations especially roll moment and vertical acceleration. Significant values in moments and vibrations can compensate the safety part of the driving and serious accident may occur